"A deep fragrance of academia": the Australian Tobacco Research Foundation. (26th November 2003) - Chapman, S; Carter, S M; Peters, M
Abstract : Objectives: (1) To review the history of the tobacco industry supported Australian Tobacco Research Foundation (ATRF)(1970–1994) for evidence of the industry's use of the Foundation to further its objectives that "more research was needed" on smoking and health and to promulgate the view that nicotine was not addictive. (2) To review efforts by public health advocates to discredit the ATRF as a public relations tool used by the Australian industry. Methods: Systematic search of previously internal industry documents released through the US Master Settlement Agreement. Results: The ATRF was headed by prestigious Australian medical scientists, with at least one considered by the industry to be "industry positive". An international ATRF symposium on nicotine was vetted by the industry and heavily attended by industry approved scientists. Following sustained criticism from the health and medical community about the industry's creation of the ATRF to further its objectives, the ATRF's scientific committee was provoked to publicly declare in 1988 that smoking was a causative agent in disease. This criticism led to growing ATRF boycotts by scientists and substandard applications, causing the industry to see the ATRF as being poor value-for-money and eventually abandoning it. Conclusions: The raison d'etre for the ATRF's establishment was to allow the Australian industry to point to its continuing commitment to independent medical research, with the implied corollary that tobacco control measures were premature in the face of insufficient evidence about tobacco's harms. Sustained criticism of tobacco industry funded research schemes can undermine their credibility among the scientific community.